1947
DOI: 10.1172/jci101832
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Gangrene Following Cold Injury. Vii. Treatment of Cold Injury by Means of Immediate Rapid Warming 1

Abstract: Hind limbs of dogs were frozen with solid CO2 and one leg was thawed at 42°C. for comparison with the other thawed at 20 to 120 C. One frostbitten ear of rabbits was thawed at 380 C. and the other at 2°C. In neither case was any essential difference reported between the rapidly and slowly thawed extremities, although the frostbitten legs were observed only for 18 hours. They reported that "if anything, the ears that were thawed in ice water showed a trace more gangrene."Ariev (1) has reported the results of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1947
1947
2004
2004

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…Frostbite produced in the ears of rabbits by immersing the part in the freezing mixture at -550 C. for 1 minute resulted invariably in the development of gangrene and the ultimate loss of all of the ear up to the line of immersion, if the ears were allowed to thaw (in air at 250 C.) without treatment. In confirmation of the work of Ariev (7), we have found that the same exposure to cold followed by immediate warming of the ear in water at + 420 C. for 2 minutes prevents the development of gangrene and loss of the injured tissue (8). In spite of the favorable end result of rapid thawing, the tissues underwent a series of changes which were grossly similar to the pregangrenous changes in the frozen, untreated ears.…”
Section: Observationssupporting
confidence: 84%
“…Frostbite produced in the ears of rabbits by immersing the part in the freezing mixture at -550 C. for 1 minute resulted invariably in the development of gangrene and the ultimate loss of all of the ear up to the line of immersion, if the ears were allowed to thaw (in air at 250 C.) without treatment. In confirmation of the work of Ariev (7), we have found that the same exposure to cold followed by immediate warming of the ear in water at + 420 C. for 2 minutes prevents the development of gangrene and loss of the injured tissue (8). In spite of the favorable end result of rapid thawing, the tissues underwent a series of changes which were grossly similar to the pregangrenous changes in the frozen, untreated ears.…”
Section: Observationssupporting
confidence: 84%
“…The results of treatment of cold injury by early mechanical control of the edema, by immediate rapid warming (12), and by the use of heparin as described by Lange and Boyd (14) all confirm the opinion of Bigelow (15) that stasis is not necessarily an irreversible process. The interruption of the transition from temporary arrest of blood flow by stasis to permanent arrest ky thrombosis may be accomplished by a variety of means.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast to the complete loss from gangrene of the part subjected to injury when no treatment is used, there is a striking reduction in the extent of gangrene following the application of a non-distensible dressing before swelling has occurred or the use of an elastic pressure dressing after swelling is maximal. In general, the amount of tissue saved by the use of measures designed to control swelling are somewhat smaller than the proportion saved by immediate, rapid warming' (12 The success or failure of treatment of cold injury by the application of casts or pressure dressings depended to an important degree upon the manner of application of the dressing and also' upon the nature of the material used for padding. Unequal distribution of pressure, especially over bony prominences, contributed greatly to the development of gangrene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During actual freezing, the tissue becomes opaque as observed by transillumination. 11 Upon thawing, appearance is normal for a short time. Edema and rupture of small vessels is then observed, particularly of small venules.…”
Section: Mechanism Of the Injurymentioning
confidence: 99%